Synthesis, Characterization and Texture Observations of Calamitic Liquid Crystalline Compounds - Qaddoura, Maher A. (Molecular Diversity Preservation International (MDPI), 2009)
Several divinylic mesogenic monomers were synthesized based on coupling the monomer 4-(4-pentenyloxy)benzoic acid with chlorohydroquinone, 2,5-dihydroxy- acetophenone, methylhydroquinone or 2-methoxyhydroquinone. This resulted in novel mesogens of phenylene esters with different lateral substituent groups. The effect of the lateral substituent group on the thermotropic phase behavior for these liquid crystalline compounds was investigated using DSC and optical polarized microscopy. All the mesogens proved to have a wide nematic liquid crystalline range. Only the phenylene ester, which has a methoxy lateral substituent, exhibited both nematic and smectic phases. Structural confirmation of all new derivatives was accomplished by (1)H- and (13)C-NMR spectroscopic analysis, along with CH elemental analysis.